(untitled) (Economic and Political Thought, 2022)
The goal of this article is to study the development of polish airport infrastructure. This study analyses situation of polish airports; presents plans of the development of polish airport infrastructure; checks fulfillment of conditions needed for building huge hub airport; describes legislative changes regarding project company for building Solidarity Transport Hub, and change of “Polish Airports” State Enterprise into “Polish Airports” Joint-Stock Company; presents issues of newly rebuilt airport in Radom, also in context of Solidarity Transport Hub.